THE EFFECT OF APPLYING TALKING CHIPS TECHNIQUE ON THE STUDENTS’ SPEAKING SKILL - Yayuk Hayulina Manurung (Journal of English Language Learning, 2019)
This research was carried due to the lack of students’ speaking skill at the first year at English department. Speaking was still frustrating and they faced some problems in learning speaking because of many factors such as shy to speak, had low motivation and less self -confidence, afraid of making mistake. Talking Chips technique is a technique of teaching speaking which make the students interested and help them speak. In the course of talking chips, each member of the group gets a chance to provide their construction and listen to the views and concerns of other member. This study aimed to investigate the effectiveness of applying Talking Chips technique on the students’ speaking skill on the first year academic of English Education Department at University of Muhammadiyah Sumatera Utara on the academic year 2019/2020. The research applied experimental research to know if there was a significant difference in speaking skill between the students taught using Talking Chips technique referred as experimental group, and the students taught using discussion method referred by control group. The data was analyzed by using t-test formula. The results of data processing on the experimental posttest and control groups showed very significant results. Thus, H1 is accepted and H0 is rejected because .000<0.05, so it can be concluded that there is a significant effect of the application of Talking Chips on students’ speaking of University of Muhammadiyah Sumatera Utara TA 2019/2010